(untitled) (Research, Society and Development, 2022)
The consumption of organic foods, when performed regularly, tends to promote additional health benefits, as they present in their composition a higher content of bioactive compounds that contribute to improving and strengthening the immune response. Therefore, this study sought to evaluate the consumption of organic food in adults during the pandemic period using a self-administered questionnaire about its conceptualization, consumption, purchase motivations and changes in eating habits during the COVID-19 pandemic. From this, it was found that most of them know what the concept of “organic food” means, however, most respondents did not start consuming during the COVID-19 pandemic. No less important, it is worth noting that among the motivations for buying this food product, the most influential factor is the benefits provided by the consumption of these foods. In addition, a significant portion of respondents (28.3% “Yes”; 48.1% “More or less”) claimed that there were changes to healthier eating habits during the pandemic.